DESAIN EKSPERIMEN TAGUCHI UNTUK MENINGKATKAN KUALITAS BATU BATA BERBAHAN BAKU TANAH LIAT - Muharom, Muharom; Siswadi, Siswadi (JEMIS (Journal of Engineering & Management in Industrial System), 2015)
Abstract A brick building material widely used in the public good urban and rural areas, the bricks used for building construction as non-structural and structural materials in the residential home building or home .As simple non-structural typically used in multi-storey buildings for insulation between rooms, or as a garnish. Community many brick-making business either continuous or seasonal production in the dry season only, that is where the problems that had been there are no standard composition of raw clay bricks. Then conducted the research as an evaluation of the composition of the constituent raw material clay, and performed statistical improvement in the manufacturing process. In the process of the experiments conducted by Taguchi approach. Taguchi experiments carried out by determining the best levels of the factors related to the quality of the bricks will be improved. From research by several factors that are taken, the most dominant factor that can increase the hardness of the brick is a mixture of the composition, the composition of the standard mixture of 90% clay, 5% bran, 5% fine sand has a hardness (voltage crushed) 57 s / to 80 kg / cm 2. By changing the composition of a mixture of 85% clay, 5% bran, 10% fine sand can increase the hardness of 89 s / d 105 kg / cm 2, and at this composition when water reproduced or softer then the resulting brick hardness can be increased again until 145 kg / cm 2.